ANALYSIS OF THE IMPLEMENTATION OF THE EVALUATION OF GUIDANCE AND COUNSELLING PROGRAM AT STATE SENIOR HIGH SCHOOLS OF SINGKAWANG - Basith, Abd. (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2017)
The objectives of this research are: (1) to describe and analyze the implementation of the guidance and counselling program at State Senior High School of Singkawang, and (2) to find some factors inhibiting the implementation of the guidance and counselling program at State Senior High School of Singkawang. This study uses qualitative methods; using interview data collecting technique, tested its validity through triangulation. The subjects in this study are all teachers of guidance and counselling in the Senior High School of Singkawang as many as 10 people as well as principals and supervisors as the informants with the total of 11 people. The data analysis techniques are in form of data reduction, presentation and conclusion. The results show that: (1) the implementation of evaluation of guidance and counselling program by the teachers still has many weaknesses on each phase of the evaluation, such as not understanding the evaluation models of the guidance and counselling program, how to apply them, and monitoring process that is not done in deeply and in detail (just what it is), (2) Some factors inhibiting the implementation of the evaluation of guidance and counselling program are lack of knowledge and understanding of the evaluation of guidance and counselling program in the schools, lack of interest in developing professional competencies, and lack of guidance to the teachers in implementing the guidance and counselling evaluation program.